Online educational counselling for students with special needs: building rapport - Margaret Debenham; Denise M. Whitelock; Pat Fung; Judy M. Emms (Association for Learning Technology, 1999)
Distance learners with long-term health problems face a number of difficulties in their studies. These include severe fatigue, problems of manual dexterity, academic and social isolation, together with a need for better interactive communication with support agencies (Debenham, 1996a). It was expected that the use of computer-mediated communication (CMC) could provide a possible way to tackle all four problems described above.